Exploring the ionic interfaces of three-electrolyte pH differential power sources. (10th October 2019) - Weng, Guo-Ming; Li, Chi-Ying Vanessa; Chan, Kwong-Yu
Abstract: Three-electrolyte configuration with two oppositely charged ion-exchange membranes can be used to yield various promising pH differential power sources. pH change, ion transport and potential profiles across the membranes and electrode/electrolyte interfaces of a three-electrolyte pH differential lead dioxide-metal hydride system are therefore systematically investigated for the first time. We find that i) pH changes of the acid and alkaline chambers are dependent on the combined effect of the electrode reaction and the ion transport. In addition, the pH change of the middle chamber is also affected by the crossover of protons from acid chamber if the anion-exchange membrane has a low permselectivity; ii) the electrical potential gradient mainly controls the ion transport with current flows; iii) the high overall cell voltage is attributed to the large pH acid-alkaline, while the potential across the membranes and electrode/electrolyte interfaces is affected by both pH and the concentration gradient. Key issues and proposed solutions are discussed to improve the electrochemical performance of this three-electrolyte pH differential electrochemical system. This work offers new opportunities to develop promising energy storage technologies. Graphical abstract: Ionic interfaces of a three-electrolyte pH differential system are studied, and feasible solutions are put forward to further improve the electrochemical performance of such a system.Image 1 Highlights: Ionic interfaces of a three-electrolyte pH differential system were studied. Adding salts into electrolyte solutions was put forward to improve the cell performance. This work offers new opportunities to develop promising energy technologies.